Adverse Selection, Diversion of Resources, and Conservatism. (5th March 2021) - Liao, Pei‐Cheng; Ma, Guang; Radhakrishnan, Suresh
ABSTRACT: We consider an investor's choice of conservative reporting, bonus payments, and investment decisions in the presence of the hidden‐information agency problem of a manager's productivity and the hidden‐action agency problem of a manager's diversion of resources. It is important to consider the hidden‐action and hidden‐information agency problems in isolation and their interaction to gain insights into the drivers of demand for conservatism. We show that the conservative (nonconservative) regime is optimal for the high‐productivity (low‐productivity) manager when both agency problems exist, even though the nonconservative regime is optimal for both the high‐ and low‐productivity managers when only the hidden‐action or the hidden‐information problem exists. Essentially, the low‐productivity manager can misrepresent as the high‐productivity manager to obtain high investment levels and divert resources only in the presence of both agency problems. This added layer of agency problem creates the demand for conservatism and highlights the importance of the interaction between the hidden‐action and hidden‐information agency problems. Furthermore, we show that as the conservatism level increases (i) the optimal investment level conditional on a good report for the high‐productivity manager increases and approaches the first‐best level (i.e., ex‐post investment efficiency increases); (ii) the expected optimal investment level for the high‐productivity manager decreases and diverges from the expected first‐best level (i.e., ex‐ante investment efficiency decreases); and (iii) the expected bonus payment to the high‐ and low‐productivity managers decreases. These findings provide insights into how the demand for conservatism arises in the presence of both hidden‐information and hidden‐action agency problems and provide empirical guidance relating conservatism to investment efficiency. RÉSUMÉ: Sélection adverse, détournement des ressources et conservatisme Nous examinons les choix d'un investisseur concernant la production de rapports financiers conservateurs, le versement de primes et les décisions d'investissement en présence d'un problème d'information cachée touchant la productivité d'un gestionnaire et d'un problème d'action cachée relatif au détournement des ressources par un gestionnaire. Il est important d'examiner les problèmes d'information cachée et d'action cachée seuls ainsi que dans le cadre de leur interaction, pour mieux comprendre les facteurs qui favorisent la demande pour une comptabilité conservatrice. Nous établissons qu'un régime conservateur (non conservateur) est optimal pour les gestionnaires productifs (peu productifs) en présence des deux problèmes, même si le régime non conservateur est optimal pour les deux types de gestionnaires lorsqu'un seul de ces problèmes est présent. En gros, les gestionnaires peu productifs peuvent, à l'instar des gestionnaires productifs, faire des déclarations erronées pour obtenir des niveaux d'investissements plus élevés et détourner des ressources seulement lorsque les deux problèmes existent. La présence simultanée des deux problèmes crée la demande pour une comptabilité conservatrice et souligne l'importance de l'interaction entre le problème d'action cachée et le problème d'information cachée. En outre, nous établissons que lorsque le niveau de conservatisme s'accroît : a) le niveau d'investissement maximal conditionnel à un rapport favorable augmente pour le gestionnaire productif et s'approche du niveau d'investissement optimal (c.‐à‐d., accroissement de l'efficacité ex post des investissements), b) le niveau d'investissement maximal attendu du gestionnaire productif baisse et s'éloigne du niveau d'investissement optimal (c.‐à‐d., diminution de l'efficacité ex ante des investissements), et c) les primes attendues pour les gestionnaires productifs et peu productifs diminuent. Ces observations nous en apprennent davantage sur la façon dont la demande pour une comptabilité conservatrice augmente en présence de problèmes simultanés d'information cachée et d'action cachée et offrent des orientations empiriques qui associent le conservatisme à l'efficacité sur le plan des investissements.